The Protection of Human Rights in Islam: As Discoursed in the Works of Al-Qaradawi - ahmad nabil amir; Tasnim Abdul Rahman (Justicia Islamica, 2017)
This paper deals with the issues of human rights as crucially discussed in the works of al-Qaradawi, such as Fatawa al-Mu”˜asarah, Fi Fiqh al-Dawlah fi al-Islam, Fiqh al-Jihad, Fiqh al-Awlawiyyat, Fiqh al-Aqalliyyat, Fiqh al-Zakah and other major contributions by him in the field of human rights. It fundamentally discussed the principle of safeguarding human rights relating to religious freedom, freedom of expression, freedom of conscience, rights of minority, gender equality, and other crucial topics substantively discussed by him. The outcome will highlight Qaradawi’s prominence as advocate of human rights and his position in this crucial issue and its contemporary relevance and significance for the ummah.